The Origin and Development of Vietnamese People’s Belief in Worshipping Mother Goddesses Three Palaces and Four Palaces: A Case Study in Thua Thien Hue Province - Phuong, Nguyen Minh; Phuc, Nguyen Huu; Binh, Nguyen Tuan; Giang, Nguyen Thi Bich; Hiep, Tran Xuan (Journal of Ecohumanism, 2024)
Vietnamese people's belief of the worship Mother Goddesses of the Three Palaces and Four Palaces formed from the worship of women in traditional culture combined with the elements "Mother Goddess Lieu Hanh ", "the Mother Goddesses of Three Realms" was “molded” from a number of discrete worship activities into a systematic belief. Currently, Vietnamese mother-worshiping custom is divided into three different forms, namely Mother-worshiping in the North, Central and South, associated with the worshiping forms, the spaces of shrines, and different ritual practices of mediumship. This distinction is shaped on the basis of historical factors and the cultural acculturation and exchange in the process of the nation's southern advance. This is quite obvious through the form of the worship of the Mother Goddesses in the Central region especially in Hue. In this article, the origin of the custom of the worship of the Mother Goddesses of the Four Palaces in Hue is clarified. In addition, the development of this belief which bears many imprints of regional cultural interference and is one of the outstanding features of Vietnamese cultural diversity is explained through each historical period.